A geochemical perspective on the hydrocarbon compositional variation within East Malay basin: Implication for oil exploration / Nurfadhila Mohd Sharef - Nurfadhila , Mohd Sharef (2020)
Malay Basin is a prospective basin which perceived to be matured basin in terms of hydrocarbon generating potential. Many significant oil discoveries made since 1970’s includes Seligi, Pulai, Tapis and Bekok oil fields. These fields have been producing until now. Despite its matured stage, there are still more oil discoveries in various parts of Malay Basin until now. Oil discoveries include light and high density oils with various challenges in oil development project. This dissertation focuses on oil fields in East Malay Basin particularly Lerek, Chermingat, Lawang and Serudon oil fields. The objectives of this research are to study the variation of oil composition in the study area and understand how these factors impact oil exploration and development project. Within the same geological setting of J reservoir, the accumulated oil property varies and influence the decision for oil development project. Lerek oil field was discovered in 1993 but currently stranded in development due to its nature of high density oil. On the contrary, Chermingat oil field which was discovered in 1992, similarly contain high density oil but has been developed successfully. Geochemical data shows that oils accumulated in shallow reservoir with temperature of lesser than 80°C within the study area are affected by biodegradation. However, it does not necessarily signify low mobility oil contributed to uneconomic oil development project. Oil production data collected from internal PETRONAS report shows that Chermingat oil which is severely biodegraded have high flow rate during production test. Systematic review was performed to understand the variation and classify the oils according to its origin based on the oil characteristics. Based on the analysis performed, results indicate that the oils are generated from source rock which was deposited in the similar environment setting. Organic matter input during source rock deposition which results in variation of wax content in oil is one of the factors that control oil property. Biodegradation is secondary process. The oil property directly affects oil mobility and flow rate which influence project economic.